Educating health science students about disability: Teachers' perspectives on curricular gaps. Issue 1 (January 2021) - Peiris-John, Roshini; Jain, Neera R.; Hogan, Amy; Ameratunga, Shanthi
Abstract: Background: People living with disabilities are significantly more likely than their peers to find health professionals' skills and facilities inadequate. The 66th World Health Assembly called for better health care for people with disabilities including more inclusive health services and a stronger focus on professional training. Objective: To explore how teachers at a New Zealand university perceived the need, approaches, and systemic challenges to enhance disability education for health professionals in training. Methods: Qualitative analysis of interviews with 11 key informants teaching in population health, medicine, nursing, pharmacy, and optometry training programmes. Transcribed interview recordings were analysed using a general inductive approach. Results: The participants described a range of teaching approaches that they used to increase disability awareness among their students. However, these were largely ad hoc individually driven initiatives reflecting personal interests. Participants identified a critical need to develop and implement a systematic, integrated approach to enhance disability education particularly from a social justice perspective among students in health disciplines. Engaging people with lived experience of disability in teaching and course design, and senior administrative commitment were identified as necessary to address current gaps in education. Conclusions: In order to develop a health professional workforce competent to respond to the needs of people with disabilities, greater attention is required at a strategic level to enhance the profile of disability education in health curricula. Meaningful engagement of people with disability and senior leadership commitment are critical components that can enable effective progression of this agenda.